Implementing Differentiated Learning Using the Problem-Based Learning Model to Stimulate Students' Problem-Solving Skills - Syarqia, Lu'lu'; Suyatna, Agus; Suana, Wayan (Asian Journal of Science Education, 2024)
The lack of implementation of differentiated learning causes teachers to be unable to accommodate students' various learning styles, which in turn reduces students' problem-solving abilities. This research aims to determine the influence of implementing content and process differentiation learning using the PBL model on improving problem-solving skills for each learning style of students and to identify the problem-solving skills that may arise from differences in learning styles. The research design used was a one-group pretest-posttest design. The research sample consisted of students in classes X-1 and X-2 at Public Senior High School Bandar Lampung in the academic year 2023/2024. The data collection method is through tests using pretest and posttest questions with indicators of problem-solving ability, and data analysis using paired difference tests (paired sample t-test) and one way ANOVA. The results of the study indicated a difference between the pretest and posttest scores of the students, where the posttest scores were higher than the pretest scores, indicating an improvement in students' problem-solving skills. The N-gain value was greater than 0.05, indicating no difference in problem-solving skills.